Automating Internship Data Management Processes in a Web-Based Application: A Case Study of FTI UNTAR - Gosal, Maria Rosa; Wasino, Wasino; Tony, Tony (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The Faculty of Information Technology at Universitas Tarumanagara (FTI UNTAR) supports the “Merdeka Belajar-Kampus Merdeka” (MBKM) industrial internship program, providing students with valuable work experiences through partnerships with companies and accessible internship listings. However, the existing management system lacks comprehensive digital support, leaving many processes manual and prone to inefficiencies, delays, and data errors. To address these challenges, this paper presents the design of a web-based application that aims to streamline internship data management by automating core processes and reducing administrative overhead. The application leverages the iterative methodology within the Software Development Life Cycle (SDLC), allowing for flexible adjustments and continuous refinement through repeated cycles of development and testing. Following development, the application successfully passed User Acceptance Testing (UAT) with all user types, including students, faculty advisors, company mentors, and administrators. Additionally, a System Usability Scale (SUS) survey conducted specifically for student users resulted in an excellent final score of 90.42, graded as A+. This outcome confirms the application’s effectiveness in enhancing operational accuracy and accessibility, elevating the overall quality of internship management at the faculty.